2016
DOI: 10.1080/10428194.2016.1231405
|View full text |Cite
|
Sign up to set email alerts
|

Impact ofABCsingle nucleotide polymorphisms upon the efficacy and toxicity of induction chemotherapy in acute myeloid leukemia

Abstract: Anthracycline uptake could be affected by efflux pumps of the ABC family. The influence of 7 SNPs of ABC genes was evaluated in 225 adult de novo acute myeloid leukemia (AML) patients. After multivariate logistic regression there were no significant differences in complete remission, though induction death was associated to ABCB1 triple variant haplotype (p = .020). The ABCB1 triple variant haplotype was related to higher nephrotoxicity (p = .016), as well as this haplotype and the variant allele of ABCB1 rs11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 38 publications
2
22
4
Order By: Relevance
“…7,[9][10][11][12] Through a linkage of clinical trial data and administrative data resources, we plan to evaluate the utility of cardiac-directed interventions on the progression and potential resolution of cardiac dysfunction. Finally, additional work is ongoing to discover and validate germline genetic variants that may predispose to anthracycline-associated cardiotoxicity and influence treatment efficacy through drug metabolism or other pharmacogenomics pathways, [27][28][29][30][31] as well as to investigate the increased risk of cardiotoxicity in black patients. A more complete understanding of the development of cardiotoxicity and effective interventions will inform evidence-based strategies to improve both the cardiovascular and oncologic outcomes for children with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…7,[9][10][11][12] Through a linkage of clinical trial data and administrative data resources, we plan to evaluate the utility of cardiac-directed interventions on the progression and potential resolution of cardiac dysfunction. Finally, additional work is ongoing to discover and validate germline genetic variants that may predispose to anthracycline-associated cardiotoxicity and influence treatment efficacy through drug metabolism or other pharmacogenomics pathways, [27][28][29][30][31] as well as to investigate the increased risk of cardiotoxicity in black patients. A more complete understanding of the development of cardiotoxicity and effective interventions will inform evidence-based strategies to improve both the cardiovascular and oncologic outcomes for children with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As consequence, a total of 35 SNPs were selected for genotyping. Although it has reported that some SNPs might affect chemotherapy efficacy in cancer patients, the evidence is not sufficient to address the role of these SNPs in survival, if only chemotherapy‐treated patients were included, unless these SNPs are also indeed involved in chemotherapy efficacy. Therefore, we first compared associations of the SNPs with survival between chemotherapy‐treated and untreated patients.…”
Section: Resultsmentioning
confidence: 99%
“…The way in which a cancer patient responds to drug treatment is dependent on many variables and among these, the individual genotype is an essential factor for influencing drug behaviour. Because of the importance of DNA repair process in determining drug sensitivity and resistance, in various cancer types, the role of polymorphisms in DNA repair genes have been explored to explain inter‐individual differences in the treatment response or survival . Many studies focused their attention on the role of PARP1 polymorphisms and their relation with increased risk for various cancer types .…”
Section: Discussionmentioning
confidence: 99%